2009
DOI: 10.1007/s11103-009-9512-z
|View full text |Cite
|
Sign up to set email alerts
|

A defensin from tomato with dual function in defense and development

Abstract: Defensins are antimicrobial peptides that are part of the innate immune system, contributing to the first line of defense against invading pathogens. Defensins and defensin-like peptides are functionally diverse, disrupting microbial membranes and acting as ligands for cellular recognition and signaling. Here we show that the tomato defensin DEF2 is expressed during early flower development. Defensin mRNA abundance, peptide expression and processing are differentially regulated in developing flowers. Antisense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 55 publications
2
62
0
1
Order By: Relevance
“…Interestingly, TPS03 promoter activity was observed in pollen grains and resembles the recently reported expression of a valencene sesquiterpene synthase in the pollen of grape (Vitis vinifera) flowers (Martin et al, 2009). A pattern of constitutive expression in reproductive organs and induced expression in vegetative tissues has also been observed for Arabidopsis geranyllinalool synthase (TPS04/GES; Herde et al, 2008) in the formation of the volatile homoterpene TMTT and has been demonstrated for other genes involved in plant defense (Pollak et al, 1993;Hoegen et al, 2002;Stotz et al, 2009).…”
Section: Tps02 and Tps03 Expression Is Under Constitutive Control In supporting
confidence: 73%
“…Interestingly, TPS03 promoter activity was observed in pollen grains and resembles the recently reported expression of a valencene sesquiterpene synthase in the pollen of grape (Vitis vinifera) flowers (Martin et al, 2009). A pattern of constitutive expression in reproductive organs and induced expression in vegetative tissues has also been observed for Arabidopsis geranyllinalool synthase (TPS04/GES; Herde et al, 2008) in the formation of the volatile homoterpene TMTT and has been demonstrated for other genes involved in plant defense (Pollak et al, 1993;Hoegen et al, 2002;Stotz et al, 2009).…”
Section: Tps02 and Tps03 Expression Is Under Constitutive Control In supporting
confidence: 73%
“…Indeed, there are already many known examples of secreted proteins or peptides with more than one function (e.g. Kuwabara and Imai, 2009;Stotz et al, 2009), almost all of which have some relationship to abiotic or biotic stress. As an aside, it should be noted that some proteins with apparent multiple functions, based on the presence of both a detectable biological activity and sequence homology to a known enzyme, may not necessarily be truly dual function, or moonlighting, proteins.…”
Section: Who Belongs To the Cell Wall Proteome?mentioning
confidence: 99%
“…S2), which in turn may lead to the decreased herbivore infestation in flowers (Damle et al, 2005). A similar scenario, which may occur in seed development, could be an OPDA-induced DEFENSIN formation known to affect seed production and embryo development (Stotz et al, 2009). Such a dual function of defense proteins in defense and development was repeatedly observed.…”
Section: Discussionmentioning
confidence: 84%
“…In developing flowers and seeds of tomato, gene expression of JA-inducible defense proteins such as PIN2 and DEFENSIN2 is up-regulated (Li et al, 2004;Stotz et al, 2009). Wild-type flowers accumulate more than 200 mg/mL soluble PIN2 protein, which is the most abundant JA-inducible protein of tomato.…”
Section: Discussionmentioning
confidence: 99%